(untitled) (Ghana Journal of Science, Technology and Development, 2024)
This paper establishes the relationship between individual citizens’ voting participation in national elections and their felt socio-economic outcomes in Ghana. The paper adopts a micro-level approach and utilises data from a random sample of 600 respondents in four electorally-swing constituencies. The aim is to ascertain their views on a range of socio-economic issues related to elections and felt individual and community outcomes. The analysis of the results was conducted using standard multi-regression. The results of the analysis established that the relationship between individual and household economic welfare related to personal income, employment opportunities, personal and household educational opportunities and personal and household health status and voting participation is varied. The conclusion is that the unique circumstances of voter participation and choice in an election in the electorally-swing constituencies in the country are contingent on superior socio-economic policies of an incumbent government or political parties in electoral competition with the aspiration to win political power and dominance in a future electoral contest in Ghana. Therefore, based on the results, the enhancement of democracy through active participation in the political and electoral processes should place a premium on inclusive access of citizens to income, health, education and employment opportunities. Keywords: elections, democracy, participation, engagement, development, voting behaviour, Ghana